Hubungan Sikap Perawat dengan Penerapan Patient Safety di Rumah Sakit Harapan Pematang Siantar Tahun 2024 - Lilis Novitarum; Imelda Derang; Debby Hutasoit (Pusat Riset dan Inovasi Nasional, 2025)
Patient safety is a hospital program that makes patient services safer and prevents incidents such as accuracy in identifying patients, improving effective communication, administering the right drugs, namely the right location, the right procedure and the right patient to minimize further risks and harm patients This type of research is a quantitative research with a cross-sectional design. The sampling technique uses purposive sampling with a total of 55 respondents. The results of the study found that the majority of nurses had an attitude in implementing patient safety in the good category as many as 52 respondents (95%) and the majority of patient safety in the good category as many as 54 respondents (98%). The results of the spearman rank test showed a p-value of 0.813 (p>0.05).. that there is no relationship between nurses' attitudes and the implementation of patient safety at Harapan Pematang Siantar Hospital in 2024.